Long‐term follow‐up of a randomized controlled trial of a text‐message diabetes self‐management support programme, SMS4BG. Issue 2 (28th November 2019) - Dobson, R.; Whittaker, R.; Jiang, Y.; McNamara, C.; Shepherd, M.; Maddison, R.; Cutfield, R.; Khanolkar, M.; Murphy, R.
Abstract: Aims: To determine the long‐term effectiveness of an individually tailored text‐message diabetes self‐management support programme, SMS4BG, on glycaemic control at 2 years in adults with diabetes with an HbA1c concentration > 64 mmol/mol (8%). Methods: We conducted a 2‐year follow‐up of a two‐arm, parallel, randomized controlled trial across health services in New Zealand. Participants were English‐speaking adults with type 1 or 2 diabetes and with an HbA1c >64 mmol/mol (8%). In the main trial participants randomized to the intervention group ( N =183) received up to 9 months of an automated tailored text‐message programme in addition to usual care. Participants in the control group ( N =183) received usual care for 9 months. In this follow‐up study, 293 (80%) of 366 randomized participants in the main trial were included. The primary outcome measure was change in glycaemic control (HbA1c ) from baseline to 2 years. Mixed‐effect models were used to compare the group differences at 3, 6, 9 and 24 months, adjusted for baseline HbA1c and stratification factors (health district category, diabetes type and ethnicity). Results: The decrease in HbA1c at 2 years was significantly greater in the intervention group [mean (sd ) –10 (18) mmol/mol or –0.9 (1.6)%] compared with the control group [mean (sd ) –1 (20) mmol/mol or –0.1 (1.8)%], with an adjusted mean difference of –9 mmol/mol (95% CI –14, –5) or –0.8% (95% CI –1.2, –0.4; P <0.0001). Conclusions: Improvements in glycaemic control resulting from a text‐message diabetes self‐management support programme were sustained at 2 years after randomization. These findings support the implementation of SMS4BG in current practice. What's new?: Innovative interventions are needed to address the growing burden of diabetes and its associated long‐term complications. Text‐messaging interventions are ideal for expanding self‐management support for people with diabetes given the ubiquity of mobile phones and their reach among people in their everyday lives where self‐management of diabetes is crucial. This study provides evidence that improvements in glycaemic control resulting from an automated text‐message diabetes self‐management support programme are sustained at 2 years. Text messaging can be an effective way of providing individually tailored support to people with diabetes outside the clinic environment.